2016
DOI: 10.3892/ijo.2016.3368
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of KiSS-1 reduces colorectal cancer cell invasion by downregulating MMP-9 via blocking PI3K/Akt/NF-κB signal pathway

Abstract: Abstract. Metastasis of colorectal cancer (CRC) depends critically on MMP-9. KiSS-1 is a human malignant melanoma metastasis-suppressor gene. Thus, the interaction between MMP-9 and KiSS-1 has drawn considerable attention in recent years. In the present study, it was hypothesized that KiSS-1 gene could repress the metastatic potential of colorectal cancer cells by inhibiting the expression of MMP-9. Stable transfection of KiSS-1 specific siRNA and KiSS-1 expression vector in human CRC cell line HCT-116 was ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 23 publications
6
31
0
Order By: Relevance
“…Overexpression of KiSS-1 also results in blockade of synthesis of MMP9 and PI3K, as well as the inhibition of phosphorylation of Akt. Furthermore, treatment with PI3K and Akt agonists attenuates the effect of KiSS-1 on the biological activity of CRC cells 24. Taken together, our results suggest that TCF21 induces Kiss-1 expression and subsequently results in downregulation of MMPs and inactivation of PI3K/AKT signaling to exert its inhibitory function on CRC.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Overexpression of KiSS-1 also results in blockade of synthesis of MMP9 and PI3K, as well as the inhibition of phosphorylation of Akt. Furthermore, treatment with PI3K and Akt agonists attenuates the effect of KiSS-1 on the biological activity of CRC cells 24. Taken together, our results suggest that TCF21 induces Kiss-1 expression and subsequently results in downregulation of MMPs and inactivation of PI3K/AKT signaling to exert its inhibitory function on CRC.…”
Section: Discussionsupporting
confidence: 51%
“…Consequently, the reduced synthesis of MMP9 induces certain inhibitory effects on the mobility and invasion of cancer cells 23. In addition, KiSS-1 treatment has been shown to elicit a strong and sustained phosphorylation of ERK1/2 and pAKT 24. Recently, Arab et al25 have found that TCF21 binds the promoter of the melanoma metastasis-suppressing gene, KiSS1 , and enhances its expression through interaction with E12 and with TCF12.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that Akt/NF-κB signaling pathway was positively correlated with tumor metastasis [20, 21]. To explore whether Akt/NF-κB signaling was also necessary for Tet-induced anti-metastatic effects on 786-O and 769-O cells, Western blotting was then performed.…”
Section: Resultsmentioning
confidence: 99%
“…Also, it has been proven as a regulator of MMP-9 to promote tumor invasion and metastasis [29, 30]. In addition, Akt signaling regulates the expression of NF-κB as well as MMP-9 in several cancer cells [20, 21]. Thus, to elucidate the effect of Tet on activation, Akt/NF-κB signaling was assessed by western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, KISS1R activation through kisspeptins may lead to suppression of ERK activation, which culminates with a reduction in matrix metalloproteinase 9 (MMP-9) expression and ultimately inhibition of tumor metastasis. 24,27 Regarding the aforementioned points, analysis of DNA methylation in EDNRB and KISS1 genes seems to be important in developing new diagnostic biomarkers; therefore, this study aims at quantitatively analyzing the methylation status of these genes in sporadic CRC patients using Methylation-Sensitive High Resolution Melting (MS-HRM) assay. Furthermore, the correlation of clinicopathological parameters and aberrant methylation of both genes will be detected.…”
Section: Introductionmentioning
confidence: 99%